-2x+7(-3x-7)=-69-3x

Simple and best practice solution for -2x+7(-3x-7)=-69-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+7(-3x-7)=-69-3x equation:


Simplifying
-2x + 7(-3x + -7) = -69 + -3x

Reorder the terms:
-2x + 7(-7 + -3x) = -69 + -3x
-2x + (-7 * 7 + -3x * 7) = -69 + -3x
-2x + (-49 + -21x) = -69 + -3x

Reorder the terms:
-49 + -2x + -21x = -69 + -3x

Combine like terms: -2x + -21x = -23x
-49 + -23x = -69 + -3x

Solving
-49 + -23x = -69 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-49 + -23x + 3x = -69 + -3x + 3x

Combine like terms: -23x + 3x = -20x
-49 + -20x = -69 + -3x + 3x

Combine like terms: -3x + 3x = 0
-49 + -20x = -69 + 0
-49 + -20x = -69

Add '49' to each side of the equation.
-49 + 49 + -20x = -69 + 49

Combine like terms: -49 + 49 = 0
0 + -20x = -69 + 49
-20x = -69 + 49

Combine like terms: -69 + 49 = -20
-20x = -20

Divide each side by '-20'.
x = 1

Simplifying
x = 1

See similar equations:

| 4x+8+8x+9=9x+3x+14 | | -7m+12+8m-3= | | 4x-24=56+2x | | (x)6=3/7 | | 4b-6=7b | | f(x)=x^3+16x^2+84x+143 | | -(-8x-6y-43)= | | 6z-8z=6z-9-z | | 7x+8-6x+4= | | 8r+6=86 | | -9(2x-3)= | | 8(6+c)=7(c-6) | | 8x+4=9(x+9) | | 56=4y+3y | | -(8-x)= | | 3n-6+6n+3=6+3n+3 | | 9(3n-2)=(8n+6)+6 | | -34=2-6y | | 75=11+6p | | 3x+17+2x-4=49-3x+36 | | -3(t-3)+6t=8t-2 | | 15z(3z-1)= | | 25x+.10y-9.45x+y=60 | | 5x+9=5(x-7) | | 24p+25p+15p+20p=840 | | 2x-1+127= | | 8x^9+7x^3-5=0 | | 4x^2-65=0 | | (2x-1)+127= | | 0.30x+0.05(90)=0.15(112) | | 25x+.10y=9.45 | | 23x+7y=19 |

Equations solver categories